Timing the tectonic mingling of ultramafic rocks and metasediments in the southern section of the coastal accretionary complex of central Chile. Issue 16 (10th December 2018) - Romero, Rurik; González-Jiménez, José M.; Barra, Fernando; Leisen, Mathieu; Garrido, Leonardo N.; Talavera, Cristina; Gain, Sarah E. M.; Griffin, William L.; O'Reilly, Suzanne Y.; Reich, Martin; Morata, Diego
ABSTRACT: Uranium-lead ages are reported for zircons from ultramafic bodies and metamorphic host rocks of the Western Series that outcrop at La Cabaña, in the southern section of the coastal accretionary complex of central Chile. Metasedimentary mica schists hosting the ultramafic bodies contain a main detrital zircon population of Devonian age (365–380 Ma) clustering around ~368 Ma, differing significantly from neighbouring areas where Devonian zircons are scarce. Zircons from the metasomatic reaction zones (albitites and chloritites), formed during the emplacement and alteration of the ultramafic bodies, are mainly Ordovician (~478 Ma) and lack Devonian zircons, resembling a typical detrital zircon pattern from other locations in the Western Series. Zircons from the chloritite reaction zone of the Lavanderos serpentinite, the easternmost ultramafic body in La Cabaña, are in textural equilibrium with metamorphic ilmenite. Some of these zircons yield an average age of 283.4 ± 7 Ma ( n  = 6) which is identical, within error, to a previously reported K-Ar fuchsite cooling age of 282 ± 6 Ma from the reaction zone. Most zircons extracted from chromitite boulders have euhedral oscillatory-zoned growth patterns with a similar range of ages than those reported for the Western Series (324–1090 Ma; n  = 12), except for two zircons with cloudy appearance and high U/Th ratios which yielded an average age of 285.5 ± 7 Ma. The presence of Early Permian zircons (~280–290 Ma) in all studied rocks suggests remobilization of Zr, possibly triggered by metasomatic fluids released during the disequilibrium reaction associated with the tectonic emplacement of the ultramafic rocks into the metasedimentary rock. Simultaneously with the formation of metasomatic zircons, Palaeozoic and Mesoproterozoic zircons from the metasedimentary rocks were mechanically incorporated into the ultramafic rocks, thus providing a record of the timing of crustal emplacement of the ultramafic rocks into the accretionary complex.